A Study on ANSYS (Workbench) Software for the Single Riveted Lap Joints: Investigating ANSYS (Workbench) Software for the Analysis and Design of Single Riveted Lap Joints (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This research is concerned with the stress examination of riveted lap joints. The existing research includes the correct design and characterisation of such joints for optimum use. Using the finite element approach, stress fracture analyzes are conducted as well as in the residual stress area actual tensile load. Using two-step procedure, the riveting phase and corresponding tensile loading of the lap joint are modeled to assess the residual and total stress level. Residual tension related to riveting is caused by intervention and clamping by the misfit system. The impact of the riveting method parameters on the tension condition was investigated by using various intervention and clamping misfit values. Two fractures, namely the semi-elliptical surface crack at the disappearing surface of the plates and also the quarter elliptical corner crack at the rivet opening, are the most commonly encountered crack forms in the riveted joints. Fracture study of broken riveted joints is conducted by applying these two types of cracks to the outer plate perpendicular to the loading. The methodology of the finite variable were used in the study of the present job. The present research has demonstrated that riveted joints are equivalent to riveted joints. The riveted joint tends to stabilize and regulate tension and to be uniformly spread. It increases the quality and longevity of the riveted joints. Modeling is performed by CATIA V 16.0 and the study of riveted lap joints can be achieved by utilizing ANSYS (Workbench) version 14.0.